Well logs reconstruction of petroleum energy exploration based on bidirectional Long Short-term memory networks with a PSO optimization algorithm - Zhang, Haoyu; Wu, Wensheng; Chen, Zhangxin; Jing, Jin (Geoenergy Science and Engineering, 2024)
During petroleum energy exploration, estimating missing well logs from existing logging data is very meaningful. Due to a highly nonlinear relationship between various logging data and a challenge to express the complexity of underground geological conditions by deterministic functions, traditional methods are difficult to meet the need of accurate interpretations of log data and fine descriptions of reservoirs. Nevertheless, deep learning method provides an advanced means for reconstructing well logs, and can directly map existing logging data to missing well logs. In this paper, we adopt the PSO-BiLSTM network that combines the BiLSTM (Bidirectional Long Short-term Memory) network with the PSO (Particle Swarm Optimization) algorithm. BiLSTM is an excellent data-driven method that can extract bidirectional temporal well logging data. PSO algorithm enhances the performance of BiLSTM model in predicting missing well logs through hyperparameter optimization, global search capability, and adaptive learning. At the same time, RMSE, MAE, and MAPE are used as indicators to evaluate the performance of PSO-BiLSTM model. The results show that when a PSO-BiLSTM model is applied to well logs reconstruction experiments, the reconstructed value of a log curve is in good agreement with its real value. Compared to LSTM and BiLSTM models, a PSO-BiLSTM model provides the best accuracy and stability in predicting missing well logs. The PSO-BiLSTM model strengthens the extraction of relevant logging information and reduces the error of parameter adjustment. It has an important reference significance for the reconstruction of well logs in complex formations. •A BiLSTM network with PSO optimization is proposed to process logging data.•PSO algorithm is introduced to optimize the hyperparameters of well logs reconstruction model.•The variation trend with depth and bidirectional temporal data of well logs can be considered.•The results confirmed that the proposed method is accurate and reliable.